Incentives for agroecological transition Doyogena region, Ethiopia: Resilient and inclusive systems - Mockshell, Jonathan; Tibebe, Degefie; Filippi, Viviane (2025)
This video - produced by the PSii project (Agroecological TRANSITIONS program) in Ethiopia - explores the critical role of crop diversity in enhancing soil health, detailing the benefits of diverse cropping systems such as improved soil structure, nutrient cycling, and beneficial microbial activity. It highlights various incentives that are encouraging farmers in Ethiopia to adopt sustainable practices, including financial support, technical assistance, and market access. Through examples and expert insights, this video demonstrates the positive outcomes of crop diversification on soil health and its importance for long-term food security and environmental sustainability. The video emphasizes the need for integrated soil fertility management, erosion control, and public-private partnerships to support sustainable farming practices.